Bridging Gender Disparity in Bangladesh: A Retake on Covid-19 Pandemic and Perspectives of Economic Opportunities - Nelufer Nazrul; Bushra Hasina Chowdhury (International Journal of Economics and Management Sciences, 2025)
During the COVID-19 pandemic, women in Bangladesh encountered higher financial crises than men. This aggravated pre-existent gender disparities in employment, income, and resource consumption. Therefore, the study investigates the extent to which the pandemic exacerbated discrepancies. It provides remedies based on proliferating electronic commerce networks. Furthermore, data from the World Bank, International Labor Organization, and UN for Women was gathered to evaluate the gender-based impact of COVID-19 on economic opportunities within Bangladesh, influencing e-commerce from an economic perspective across Bangladesh. The research findings reveal that Bangladesh possesses the potential to encompass electronic commerce within economic settings and empower women to engage in economic projects. Furthermore, the research recommends focusing on different cultural and policy settings to create further economic opportunities in Bangladesh. Future studies should attempt to study the effects of infrastructure and cultural norms on e-commerce and its potential to bridge the gender gap across varying regional settings.